Developing computer competencies for eWorkers within call centres. - Kirk, Elizabeth; Strong, Jenny; Burgess-Limerick, Robin (Work, 2013)
High rates of work related musculoskeletal discomfort (WRMSD) associated with long-hours of computer work are considered a significant occupational health problem. However, to date few training programs aim to develop the multidisciplinary skills required for self-management of WRMSD risk factors. This paper seeks to provide a background to, and illustrate the significance of, this issue. Management strategies, training elements and methods recommended within the literature to build the required work skills for increased self-management of WRMSD are discussed. The inclusion of two case studies investigating the impact of training methods on levels of WRMSD illustrates how the application of new training strategies may improve WRMSD outcomes. The first case-study trialling a pre-existing office ergonomic checklist revealed training improved knowledge and awareness, but failed to change work behaviours or effect levels of WRMSD. The second case study investigated the impact of training providing additional knowledge and demonstrating 'how-to' apply recommendations at the workstation. Outcomes of this skill-based program included the collaborative development of training elements, increased trainee engagement, and a significant reduction in reported levels of WRMSD. These findings suggest training designed to develop multidisciplinary work skills or competencies may be a strategy for the management of occupational musculoskeletal discomfort amongst computer operators.